Contribution de la philosophie de Nicolas Grimaldi à la réflexion éducative - Yoann Daumet (Éducation et Socialisation)
In a context of issues about the interest of introducing spirituality into school, this article offers a philosophical reflection on what could still be called the school’s essential spirituality. This spirituality was a central dimension of classical republican thought. It was part of a humanistic faith and seems to have been swept away by the criticism of this humanism by the human sciences to the point that founding a secular spirituality of the school may seem today a challenge. The philosophy of Nicolas Grimaldi, reinterpreting the relationship of the spirit and nature in a split monism and an ontology of life can help to overcome it. In the light of the ethics that this philosopher draws from this ontology, this article defines a scholar spirituality and the teacher’s work.